Gestión administrativa y logística de la transportación de carga pesada y su incidencia en tiempos de inseguridad en la provincia de los Ríos, año 2023. - Rodríguez Morán, Leila Madeleine (2024)
The administrative and logistical management of heavy cargo transportation is crucial for the efficiency of the supply chain, especially in insecure contexts, where challenges such as theft and damage to cargo are faced. This study aims to evaluate the administrative and logistical management of heavy cargo transportation and its incidence in times of insecurity in the province of Los Ríos during the year 2023. The methodology used includes a mixed approach, combining surveys directed to the president of the Union of Heavy Cargo Transport Operators, interviews with representatives of various companies and secondary analyzes to understand insecurity patterns. Key aspects such as the planning of safe routes, the implementation of tracking and monitoring systems, and the effective coordination between the different actors in the logistics chain were investigated. The results reveal that insecurity on the roads, especially in critical areas such as the Quevedo ring road and areas near Guayaquil, represents a significant challenge that affects the safety of carriers and operational profitability. A substantial economic impact was identified due to theft and ransom payments, affecting approximately 30% of members. Coordination with local and government authorities, such as the Ecuadorian Traffic Commission and the National Police, is crucial to implement effective and sustainable security measures. Furthermore, deteriorating roads and lack of proper maintenance further complicate the situation, highlighting the need to improve road infrastructure.